(untitled) (diségno, 2023)
On Wednesday, June 26, 2019, a farewell event was held at the Triennale, in Milan, for the celebrated architecture magazine San Rocco, which had passed away prematurely –the initial plan was for 20 issues to be published– with the 15th issue dedicated, fittingly, to the theme of ‘Death’. San Rocco was, at a global level, one of the most successful publishing experiences of the last 20 years in the field of architecture. A magazine printed in 3,000 copies, almost always sold out. A kind of publishing miracle for an independent magazine, produced in Italy and dedicated to the autonomy of architecture, a discipline notoriously in a tragic condition, at least in this country. [read more]